AN ANALYSIS ON THE CAUSE OF STUDENTS' SPEAKING ANXIETY IN EFL CLASSROOM - Nurilahi, Reski; Suhartono, Luwandi (FKIP - Universitas Tanjungpura, 2022)
Speaking is one of four skills that are deemed to be important. In EFL Classroom, the students often suffer from English speaking anxiety. The purpose of this research was to discover the level of students